MODEL OF SCHOOL PRINCIPAL ACADEMIC SUPERVISION BASED ON LESSON STUDY - Nana Mulyana; Aang Abdulah Zein; Rahmat Mulyana; Ade T utty R Rossa; Deti Rostini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper analyzes the lesson study-based school principal academic supervision model to improve the pedagogical competence of teachers at SDN Cipanengah CBM Sukabumi by using a qualitative descriptive research method. The research was conducted by analyzing the stages of Plan, Do, and See. The research begins with interviews and field observations. Planning indicators are 1) identifying plans, 2) formulating objectives and output criteria, 3) compiling schedules, 4) reviewing instruments, 5) carrying out supervision, 6) carrying out supervision of learning outcome assessments, 7) analyzing results, 8) designing the provision of feedback, 9) preparing follow-up planning, and 10) preparing supervision reports. Indicators of implementation and observation are 1) reviewing device administration, 2) reviewing the implementation plan, 3) carrying out supervision, and 4) carrying out assessment supervision of learning outcomes. Indicators of reflection include 1) assessment supervision observation, 2) analysis, 3) academic supervision data analysis, and 4) follow-up. Management of academic supervision is indispensable to increasing teachers’ pedagogical competence. Based on the results of interviews and field observations, it is found that nearly 75.63% had sufficient criteria in making administration of learning tools and carrying out assessment activities.